Design, analysis and fabrication of an escalator model for educational purposes / Ahmad Harith Abdullah, Ilya Izyan Shahrul Azhar and Miqdad Khairulmaini - Abdullah, Ahmad Harith; Shahrul Azhar, Ilya Izyan; Khairulmaini, Miqdad (School of Mechanical Engineering, 2022)
To understand subjects that are technical, it is very helpful to have a working model for the intended subject. Having a model will help students to better visualise and understand the operation. Escalators can virtually be found in every shopping complex and tall building. However, understanding how escalators work is very difficult by just simply observing them. The aim of this project is to design and fabricate a working model of an escalator for educational purposes. Designing the escalator involves referring to drawing standards of an actual escalator to ensure that important elements are included. Based on the final design, the model was then fabricated using the appropriate fabrication processes. The result from this project was a working model of an escalator which helps show the actual working operation. The model helped students to better understand its working operation. The model is very user-friendly as it is easy to operate and is suitable for anyone in the educational sector